Impact of Entrepreneurial Education on Entrepreneurial Intention of Students : Analysis of Bhutanese Business Colleges - Haridev Singh, Elangbam; Drakpa, Dawa (AMC Indian Journal of Entrepreneurship, 2023)
It has been observed that youth unemployment and entrepreneurship are two sides of a coin in the context of Bhutan. Entrepreneurship education initiatives in Royal University of Bhutan (RUB) target motivating Bhutanese youths towards entrepreneurship despite their general preference for white-collared jobs or civil service jobs. Thus, this research tried to focus on influence of entrepreneurship education on entrepreneurship intentions among undergraduate business students in Bhutan. The most widely used Theory of Planned Behaviour has been utilized for the study taking into consideration the mediating role of the factors subjective norms, attitudes towards entrepreneurship, and perceived behavioural control. For testing these assumptions, data were collected from 427 students of three business colleges in Bhutan. The findings suggest that all three dimensions of Theory of Planned Behaviour show significant association with entrepreneurial intention. Although the correlation and regression analysis support the hypotheses, not all the dimensions play the same part in influencing entrepreneurship intention (EI).